Breastfeeding practices that support women with diabetes to breastfeed. Issue 1 (October 2015) - Fallon, Anne; Dunne, Fidelma
Highlights Breastfeeding as the first feed following birth is beneficial. The woman's collective diabetes, breastfeeding and infant's needs require consideration. An early first breastfeed is recommended. Care from an informed multidisciplinary team is supportive. Guidance to deal with common breastfeeding concerns is encouraged.